PENGARUH GAYA KEPEMIMPINAN, KUALITAS KEHIDUPAN KERJA, DISIPLIN KERJA, AUDIT SUMBER DAYA MANUSIA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA PT. PJB UBJOM PLTU TENAYAN) - Al’Afif, Salim; Rodiah, Siti; Suriyanti, Linda Hatri (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2018)
The purpose of this study was to examine the study of leadership style, quality of work life, work disciplin, human resource audits and compensation for employee work productivity. The population in this study were employees who worked at PT. PJB UBJOM PLTU Tenayan in Pekanbaru Riau Provinsi. The sample of study was 98 respondent. The sampling method in this study was saturated sample. The data used in this study is primary data, which is done using a survey method with questionnaires. The processing method carried out is multiple linear regression. Based on the results of the study, it can be concluded that the variables of leadership style, quality of work life, work disciplin and human resource audits negatively affect employee work productivity. While the compensation variable has a positive effect on employee work productivity.